Multiresolution FDA-SAR Imaging Method Based on Sub-band Shifting - Keyi WANG; Jingwei XU; Guisheng LIAO; Weiwei WANG (Leida xuebao)
In this paper, a Frequency Diverse Array (FDA)-based Synthetic-Aperture Radar (FDA-SAR) imaging method based on sub-band shifting and splicing is proposed to address the conflicting issues associated with multi-mode SAR imaging in parameter design, such as those related to resolution and imaging swath. Using the multiple-sub-band concurrent mode of a FDA radar, a radar waveform with an adjustable bandwidth is designed. The time-frequency-domain expressions of the synthesized signals with arbitrary bandwidths are derived in detail, enabling compensation for the involved azimuth-time-delay differences and inconsistent frequency bands. The effect of the spectrum distribution of the synthesized signals on the imaging performance is analyzed, and spectrum synthesis based on non-uniform sub-band shifting is adopted, which reduces the peak sidelobe level and improves the imaging performance. Finally, simulations verify the effectiveness of the proposed method to simultaneously achieve signal-level fusion processing for coarse-resolution imaging of large observation scenes and fine-resolution imaging of key areas.